REHABILITASI BAGI PENGGUNA NARKOBA DALAM PANDANGAN HUKUM ISLAM - Syaflin Halim (LPPM Universitas Muhammadiyah Sumatera Barat, 2019)
This research is based on the phenomenon of narcotics abuse which is increasingly rampant, while the handling is not enough. The problems that arise are differences in perceptions among law enforcement officers which then lead to the handling of different drug abusers. There is a tendency to punish narcotics addicts with criminal penalties. Whereas there is still a sanction of choice that is rehabilitation. Based on the background of the problem, the focus of this research is how the position of rehabilitation as a sanction in view of Islamic law. The results of this study reveal that (1). Sanctions for addicts and victims of drug abuse in the perspective of Islamic criminal law, when prosecuted through the approach of hudud sanctions, can be transferred to rehabilitation, on the basis of judges' considerations and there are elements syubhat, namely the element of uncertainty, uncertainty and doubt in the proof of drug use, Confusion in certain chapters.In accordance with maqasidshari'ah rehabilitation aims to rejuvenate physically in accordance with hifz an-nafs, restore the health of reason according to hifs al-aql. Rehabilitation can also use a religious approach to implementing hifzal-din. After completion of rehabilitation process and the perpetrators have returned to the proper life then there has been efforts hifz al-mal and hifz an-nasl. Key word: Rehabilitation, Drug Abuse, Islamic Law